2006
DOI: 10.1111/j.1462-5822.2006.00785.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-apoptotic signalling by the Dot/Icm secretion system ofL. pneumophila

Abstract: SummaryThe Dot/Icm type IV secretion system of Legionella pneumophila triggers robust activation of caspase-3 during early and exponential stages of proliferation within human macrophages, but apoptosis is delayed till late stages of infection, which is novel. As caspase-3 is the executioner of the cell, we tested the hypothesis that L. pneumophila triggers antiapoptotic signalling within the infected human macrophages to halt caspase-3 from dismantling the cells. Here we show that during early and exponential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
179
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(188 citation statements)
references
References 97 publications
(162 reference statements)
6
179
2
1
Order By: Relevance
“…These observations indicate that an apoptotic process is initiated in macrophages in response to L. pneumophila infection and replication, but the bacteria are able to inhibit or reverse the process in a Dot/Icm-dependent manner, possibly by injecting effectors that can interfere with apoptotic pathways. Consistent with this hypothesis, two recent studies showed that a large number of antiapoptotic genes were induced in cells infected by virulent L. pneumophila strains via the activation of the multifunctional transcriptional regulator NF-B (17,18). Moreover, the Dot/Icm substrate SdhA was recently shown to be required for protecting macrophages from cell death by a yet-unknown mechanism (19).…”
supporting
confidence: 50%
See 2 more Smart Citations
“…These observations indicate that an apoptotic process is initiated in macrophages in response to L. pneumophila infection and replication, but the bacteria are able to inhibit or reverse the process in a Dot/Icm-dependent manner, possibly by injecting effectors that can interfere with apoptotic pathways. Consistent with this hypothesis, two recent studies showed that a large number of antiapoptotic genes were induced in cells infected by virulent L. pneumophila strains via the activation of the multifunctional transcriptional regulator NF-B (17,18). Moreover, the Dot/Icm substrate SdhA was recently shown to be required for protecting macrophages from cell death by a yet-unknown mechanism (19).…”
supporting
confidence: 50%
“…Such modulation can occur at the transcriptional level because infection by L. pneumophila leads to the induction of several antiapoptotic genes via the activation of an NF-B-dependent pathway (17,18). Transcription of a number of pro-death genes, including the BH-3-only protein BNIP3 and many caspases, also was elevated in response to intracellular growth of the bacterium (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second facet of innate immunity that controls cytokine transcription and is triggered by L. pneumophila infection in murine and human cells is signaling through NF-B (32,33,(35)(36)(37)(38)(39). Thus, we assessed levels of I B␣, the inhibitor of NF-B that keeps the transcription factor sequestered in the cytoplasm of the cell.…”
Section: Resultsmentioning
confidence: 99%
“…Although the killing of target cells may play some role in the pathogenesis of disease within the animal, host cell death is distinctly antagonistic to intracellular replication (23), and it is known that the bacterium limits host cell death by the induction of macrophage anti-apoptotic proteins (24). L. pneumophila, however, also uses other strategies to interfere with host cell death, as there seem to be Dot/Icmdependent signals that antagonize host cell death (25).…”
mentioning
confidence: 99%